Value of fibrolaparoscopy in the staging of gastric cancer - Praderi, Luis A.; Atilio, Antonio; Ribeiro, Martha (Cirugía del Uruguay, 1993)
The authors study the value of fibro/aparoscopy in the determination of the degree of abdominal lesiona/ extension in gastric cancer cases by means of the prospective study of 47 patients. They a/so analyse the utility of that information for avoidance of negative laparotomies. The results encourage the use of this procedure. The future determined by the appearance of videolaparoscopy in the field of diagnostic fibrolaparoscopy remains established.